Selective IL-13 inhibitors for the treatment of atopic dermatitis - Francisca Gonçalves; Egídio Freitas; Tiago Torres (BioExcel Publishing Ltd, 2021)
Background: Atopic dermatitis (AD) is one of the most common chronic inflammatory skin diseases worldwide. AD pathogenesis is multifactorial, involving environmental and genetic factors. IL-13 stands out as one of the main cytokines in the pathophysiology of AD. Currently, dupilumab, which targets both IL-4 and IL-13 signalling, is the only biologic agent approved for the treatment of moderate-to-severe AD. New targeted biologic therapies are being developed, such as lebrikizumab and tralokinumab, two selective IL-13 inhibitors. This article reviews the role of IL-13 in AD and the most recent data on lebrikizumab and tralokinumab. Methods: A narrative review of the literature was written after retrieving relevant articles in the PubMed database (up until December 2020) using the following keywords present in the title, abstract or body: atopic dermatitis; interleukin 13; IL-13; tralokinumab; lebrikizumab, biologic therapy. Discussion: A phase IIb trial showed that all three dosing regimens evaluated (lebrikizumab 125 mg every 4 weeks (Q4W), 250 mg Q4W or 250 mg every 2 weeks) achieved rapid and dose-dependent efficacy concerning the signs and symptoms of AD, with a statistically significant improvement, at week 16. Tralokinumab was studied in three phase III clinical trials and reached its primary endpoints at week 16 (ECZTRA 1 and 2 in monotherapy and ECZTRA 3 with concomitant topical corticosteroids), with response maintained over time. Both lebrikizumab and tralokinumab exhibited good safety profiles in AD trials, with adverse effects usually being comparable between the control and treatment groups. Conclusion: The evidence supports the hypothesis that selective antagonism of IL-13 is sufficient to control AD, providing an improvement in the patient's quality of life. Therefore, the development of lebrikizumab and tralokinumab represents a new and exciting phase in the management of AD.